2020
DOI: 10.1152/ajpheart.00354.2020
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of prolonged sitting with mild hypercapnia on vascular and autonomic function in healthy recreationally active adults

Abstract: Prolonged sitting, which is known to impair peripheral vascular function often occurs in spaces (e.g. offices) with mild hypercapnic atmospheres. However, the effects of prolonged sitting in hypercapnic conditions on vascular function are unknown. Therefore, the purpose of this study was to investigate the effects of prolonged sitting in mild hypercapnic conditions on vascular and autonomic function in humans. Methods: 12 healthy young adults participated in two experimental visits which consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 95 publications
3
45
0
Order By: Relevance
“…Of these, 29 randomized cross-over trials underwent full text screening and 8 were excluded (Chaput and Tremblay, 2007 ; Bourdin et al, 2010 ; Jean-François et al, 2010 ; Larsen et al, 2014 ; Restaino et al, 2015 ; Botter et al, 2016 ; Garten et al, 2018 ; Snarr et al, 2019 ). The final analysis included 22 studies (27 trials) with 21 studies reporting HR data (Shvartz et al, 1983 ; Chowienczyk et al, 1994 ; Higgins et al, 2011 , 2019 ; Thosar et al, 2012 ; De Brito et al, 2015 ; Restaino et al, 2015 ; Wennberg et al, 2016 ; Barone Gibbs et al, 2017b ; Cabak et al, 2017 ; Vranish et al, 2017 ; Carter et al, 2018 ; Garten et al, 2018 ; Horiuchi et al, 2018 ; Sperlich et al, 2018 ; Credeur et al, 2019 ; Dogra et al, 2019 ; Evans et al, 2019 ; Kowalsky et al, 2019 ; Cheng-Hsuan et al, 2020 ; Headid et al, 2020 ) and seven studies reporting HRV data (Shvartz et al, 1983 ; Chowienczyk et al, 1994 ; Thosar et al, 2012 ; Restaino et al, 2015 ; Cabak et al, 2017 ; Kruse et al, 2018 ; Credeur et al, 2019 ). Additionally, 13 of the HR studies reported interruption conditions to the bout of prolonged sitting (De Brito et al, 2015 ; Wennberg et al, 2016 ; Barone Gibbs et al, 2017b ; Cabak et al, 2017 ; Vranish et al, 2017 ; Carter et al, 2018 ; Garten et al, 2018 ; Kruse et al, 2018 ; Sperlich et al, 2018 ; Dogra et al, 2019 ; Evans et al, 2019 ; Kowalsky et al, 2019 ; Headid et al, 2020 ), however there were not enough HRV studies reporting interruption conditions (Cabak et al, 2017 ; Kruse et al, ...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, 29 randomized cross-over trials underwent full text screening and 8 were excluded (Chaput and Tremblay, 2007 ; Bourdin et al, 2010 ; Jean-François et al, 2010 ; Larsen et al, 2014 ; Restaino et al, 2015 ; Botter et al, 2016 ; Garten et al, 2018 ; Snarr et al, 2019 ). The final analysis included 22 studies (27 trials) with 21 studies reporting HR data (Shvartz et al, 1983 ; Chowienczyk et al, 1994 ; Higgins et al, 2011 , 2019 ; Thosar et al, 2012 ; De Brito et al, 2015 ; Restaino et al, 2015 ; Wennberg et al, 2016 ; Barone Gibbs et al, 2017b ; Cabak et al, 2017 ; Vranish et al, 2017 ; Carter et al, 2018 ; Garten et al, 2018 ; Horiuchi et al, 2018 ; Sperlich et al, 2018 ; Credeur et al, 2019 ; Dogra et al, 2019 ; Evans et al, 2019 ; Kowalsky et al, 2019 ; Cheng-Hsuan et al, 2020 ; Headid et al, 2020 ) and seven studies reporting HRV data (Shvartz et al, 1983 ; Chowienczyk et al, 1994 ; Thosar et al, 2012 ; Restaino et al, 2015 ; Cabak et al, 2017 ; Kruse et al, 2018 ; Credeur et al, 2019 ). Additionally, 13 of the HR studies reported interruption conditions to the bout of prolonged sitting (De Brito et al, 2015 ; Wennberg et al, 2016 ; Barone Gibbs et al, 2017b ; Cabak et al, 2017 ; Vranish et al, 2017 ; Carter et al, 2018 ; Garten et al, 2018 ; Kruse et al, 2018 ; Sperlich et al, 2018 ; Dogra et al, 2019 ; Evans et al, 2019 ; Kowalsky et al, 2019 ; Headid et al, 2020 ), however there were not enough HRV studies reporting interruption conditions (Cabak et al, 2017 ; Kruse et al, ...…”
Section: Resultsmentioning
confidence: 99%
“…Seven trials included clinical populations with cardiometabolic diseases including one trial with hypertensive participants (Credeur et al, 2019 ), four trials with overweight/obese participants (Vranish et al, 2017 ; Garten et al, 2018 ; Dogra et al, 2019 ; Kowalsky et al, 2019 ), and two trials with both hypertension and overweight/obese participants (Wennberg et al, 2016 ; Carter et al, 2018 ). Bouts of prolonged sitting ranged from 1 (Headid et al, 2020 ) to 9 (Dogra et al, 2019 ) h with an average duration of 5 h. It should also be noted that all HRV studies (Shvartz et al, 1983 ; De Brito et al, 2015 ; Vranish et al, 2017 ; Carter et al, 2018 ; Garten et al, 2018 ; Wheeler et al, 2019 ) l for <3 h, which was characterized as a short bout of sitting. Of the 22 trials, 13 included interruptions to sitting (De Brito et al, 2015 ; Wennberg et al, 2016 ; Barone Gibbs et al, 2017b ; Cabak et al, 2017 ; Vranish et al, 2017 ; Carter et al, 2018 ; Garten et al, 2018 ; Kruse et al, 2018 ; Sperlich et al, 2018 ; Dogra et al, 2019 ; Evans et al, 2019 ; Kowalsky et al, 2019 ; Headid et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations